Prediction of outcomes after chemoradiotherapy for cervical cancer by neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio - Jing Yu; Longzhang Huang; Ting Dong; Lihua Cao (Journal of Obstetrics and Gynaecology)
Background Cervical cancer ranks as the second most fatal tumour globally among females. Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been widely applied to the diagnosis of cancers.Methods The clinicopathologic data of 180 patients with stage IB2-IIB cervical cancer who underwent radical concurrent chemoradiotherapy from January 2018 to December 2019 were retrospectively analysed. Receiver operating characteristic (ROC) curves were plotted to analyse the optimal cut-off values of NLR and PLR for predicting the therapeutic effects of concurrent chemoradiotherapy. The associations of PLR and other clinicopathological factors with 1-year survival rates were explored through univariate analysis and multivariate Cox regression analysis, respectively.Results NLR was significantly associated with the therapeutic effects of neoadjuvant therapy, with the optimal cut-off value of 2.89, area under the ROC curve (AUC) of 0.848 (95% confidence interval [CI]: 0.712–0.896), sensitivity of 0.892 (95% CI: 0.856–0.923) and specificity of 0.564 (95% CI: 0.512–0.592). PLR had a significant association with the therapeutic effects of neoadjuvant therapy, with the optimal cut-off value of 134.27, AUC of 0.766 (95% CI: 0.724–0.861), sensitivity of 0.874 (95% CI: 0.843–0.905) and specificity of 0.534 (95% CI: 0.512–0.556). Lymphatic metastasis ([95% CI: 1.435–5.461], [95% CI: 1.336–4.281], depth of invasion ([95% CI: 1.281–3.546], [95% CI: 1.183–3.359]) and tumour size ([95% CI: 1.129–3.451], [95% CI: 1.129–3.451]) were independent factors influencing the overall survival and disease-free survival (DFS) of patients with cervical cancer. NLR (95%CI: 1.256-4.039) and PLR (95%CI:1.281-3.546) were also independent factors affecting DFS.Conclusion NLR and PLR in the peripheral blood before treatment may predict DFS of patients with stage IB2-IIB cervical cancer.